Tourism and development; a case study of the Commonwealth Caribbean - Bryden, John M. (Cambridge [Eng.] University Press, 1973)
This book examines the tourism industry's economics in the Caribbean. It discusses the social and political factors connected with the industry in addition to the economic analysis. It tend to portray a picture of an industry with no great economic value. The potential benefits to developing countries may be apparent to many, but the discussion on them is invariably confused.
Based on the author's thesis, University of East Anglia.
Bibliography: p. 222-227.
II 16/01/2019
Loans
Keywords: Tourism; Economic conditions; Caribbean